Argumen al-Qur'an dan Hadisty tentang Partisipasi Perempuan di Ruang Publik - Prihatini, Rini L. (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2011)
Working ooutside the home (public space) is important for women. For women who work outside she will be more flexible in the budgeting the financial the needs of her children, self, and others. what ever the motivations are, women who work in public spaces, provide significant contribution for themsel ves and their families. often women should undergo double job, household and public works. is there a basic in Islamic teachings that allow women to work ? al-qur'an verses (al-Qashash 23 and al-Nisa 32) clearly state women should work outside either independently or in groups, in private or government agency, day or night, as long as the work is conducted in a dignified atmosphere, the women are able to maintain what is taught by the religion and they can avoid the negative impact of the job either for themselves or their environment.